Identification of motility clusters per area in surfaces colonized by Pseudomonas aeruginosa - Guzmán, M. (2011)
The biofilms are involved in pathogenesis and antibiotic persistence and resistance. The number of cells of a given species that will adhere to surfaces depends not only on the affinity of the cells but also on their number available for attachment. Therefore, the quick identification of the motile microorganism's area should be of great interest. The analysis of bacterial spatial patterns at the initial stage of biofilm formation is very important to know the success of the bacterial colonization. We propose a post processing method capable to distinguish motile microorganisms area of colonization in dynamic speckle images by applying Mathematical Morphologic techniques. The methodology would be effective for segmenting, detecting and describing patterns of colonization known not to be completely spatially random. The presented method is fast, reproducible, convenient, robust, and can be used to control the pattern, spacing, and orientation between colonies of different bacteria in order to prevent biofilm development.